PERAN KEPEMILIKAN MANAJERIAL SEBAGAI MODERASI DALAM PENGARUH CEO NARSISME, BOARD GENDER DIVERSITY DAN CASH HOLDING TERHADAP MANAJEMEN LABA PERUSAHAAN - Ferra Maryana; Ferli Erwansyah (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aims to give empirical evidence about the moderating role of managerial ownership on the influence of CEO narcissism, board gender diversity and cash holding on profit management of primary consumer goods sub-sector companies listed on the IDX in 2019-2022. The research method used is quantitative. The research population is primary goods and consumer companies. The research sample is 15 companies. The research analysis uses logistics The research results prove that CEO narcissism and board gender diversity do not have a direct effect on earnings management, only cash holding has a direct effect on earnings management. Managerial ownership moderates the influence of board gender diversity and cash holding on earnings management, but is unable to moderate the influence of CEO narcissism on earnings management.